Is the new AquaTrainer® snorkel valid for VO2 assessment in swimming? - Baldari, C.; Fernandes, R. J.; Meucci, M.; Ribeiro, J.; Vilas-Boas, J. P.; Guidetti, L. (International Journal of Sports Medicine, 2013)
The Cosmed AquaTrainer® snorkel, in connection with the K4b2 analyzer, is the most recent instrument used for real time gas analysis during swimming. This study aimed to test if a new AquaTrainer® snorkel with 2 (SV2) or 4 (SV4) valves is comparable to a standard face mask (Mask) being valid for real time gas analysis under controlled laboratory and swimming pool conditions. 9 swimmers performed 2 swimming and 3 cycling tests at 3 different workloads on separate days. Tests were performed in random order, at constant exercise load with direct turbine temperature measurements, breathing with Mask, SV4 and SV2 while cycling, and with SV2 and SV4 while swimming. A high agreement was obtained using Passing - Bablok regression analysis in oxygen consumption, carbon dioxide production, tidal volumes, pulmonary ventilation, expiratory fraction of oxygen and carbon dioxide, and heart rate comparing different conditions in swimming and cycling. Proportional and fixed differences were always rejected (95% CI always contained the value 1 for the slope and the 0 for the intercept). In conclusion, the new SV2 AquaTrainer® snorkel, can be considered a valid device for gas analysis, being comparable to the Mask and the SV4 in cycling, and to the SV4 in swimming.